Morphological variations of the condylar head among children aged 4-15 years: A panoramic study - Rahul Hegde; Anand Shigli; Pritesh Gawali; Aishwarya Krishnan; Geetanjali Jadhav; Soniya Raheja (Wolters Kluwer Medknow Publications, 2021)
Background: Growth and development of dentocraniofacial complex occurs during various stage of development of dentition with TMJ as one of its centres of growth. The condition of temporomandibular joint can be visible from its condylar head form; therefore, it is crucial to recognize the normal morphology of condylar head during different stages of development of dentition. Aims: The aim of the study is to view the morphological appearance of condylar head during primary dentition, mixed dentition and permenant dentition. Subject and Methods: 400 panoramic images of 194 boys and 296 girls were collected and were divided into three groups bases on the stage of dentition. Shape of the condylar head were determined by tracing the print out of the panoramic image on an X ray viewer. Results: The study showed that during primary dentition stage shape of the conylar head was dominated by round shape and as growth and development occurs the condylar head shape changes to convex. Conclusion: The study describes the normal morphology of mandibular condyles in a child population attending The dentition status as well as growth of craniofacial has a significant role in determining condylar morphology.